Inequalities in maternal malnutrition in Ethiopia: evidence from a nationally representative data - Nigatu Regassa Geda (BMC, 2021)
Abstract Background Despite promising progress made in several maternal health indicators, maternal malnutrition (especially undernutrition) remained one of the greatest development challenges for Ethiopia. The main purpose of this study was to examine the disparities in maternal malnutrition and estimate the population level impacts of key risk factors in Ethiopia. Methods The analysis was made based on the Ethiopian Demographic and Health Survey (EDHS 2016) data, containing 9949 non-pregnant women. Multiple logistic regression was used to examine the effects of selected explanatory variables on the two nutrition morbidity outcomes (undernutrition and obesity). Two population weighed regression-based measures (the Slope Index of Inequality/SII and Relative Index of Inequality/RII) and Population Attributable Fractions (PAFs) were employed to examine the inequalities in maternal malnutrition. Results The prevalence of maternal undernutrition and overweight or obesity were 21% and 6%, respectively. In the multiple logistic regression, four variables appeared to have significant association with both undernutrition and overweight/ obesity, namely age of the women, residence, maternal education, and non-monetary wealth (p < 0.05). Both the absolute and relative measures of inequalities showed remarkable differences in maternal undernutrition, significantly favoring the higher socioeconomic groups (p < 0.05). Further analysis of inequalities, using the Population Attributable Fractions (PAFs), revealed that the combined population level impacts of all the significant risk factors amount 80.38%, from which 25% is attributed to the three socioeconomic variables (non-monetary wealth, maternal education and paternal education). Conclusion and policy implication Given the high disparity in both under nutrition and overweight and/or obesity, the study emphasized the need for policy and program efforts to promote parental education in Ethiopia. Strengthening nutrition sensitive mass literacy programs is recommended along with improving women's employment and rural households' income for increased access to better diet.